Dominant inverse nonlinear energy cascades in coastal and inner shelf waters - Annalisa De Leo; Chang He; Alessandro Stocchino (Proceedings of the National Academy of Sciences, 2026)
As well known, almost 80% of the total oceanic kinetic energy is contained within the mesoscale eddies, but the cross-scale energy transfers linking eddy generation and dissipation remain an open question. The Earth rotation controls the generation of mesoscale eddies that transfer energy toward larger scales via an inverse cascade, but a transfer to small scale is needed for dissipation: a coexistence of transfers is indeed required. However, the turbulent energy cascade, responsible for oceanic circulation energy balance and nutrient mixing, involves such a large range of scales making extremely challenging the investigation of the full spectrum of processes. This study examines how energy and enstrophy cascade across ocean scales in the inner shelf of the Great Bay Area of the South China Sea using high-resolution numerical simulations. By applying coarse-graining techniques, the results reveal a predominant inverse energy cascade scenario driven by the interplay between background stratification and rotation, particularly in areas affected by the Pearl River’s freshwater influx. Geographical heterogeneity significantly influences these dynamics, with shallow inlets experiencing increased frictional drag and energy dissipation due to complex bathymetry, while open-water areas show heightened submesoscale activity. Seasonal monsoon cycles further modulate these processes, with summer winds amplifying nonlinear energy transfers through increased wind stress and river discharge, in contrast to the tidally dominated, quasi-steady flows observed in winter. Understanding how wind and tide affect ocean mixing can help to develop more accurate climate models and better strategies for protecting coastal ecosystems.